Construction of Mussel-Inspired Dopamine–Zn2+ Coating on Titanium Oxide Nanotubes to Improve Hemocompatibility, Cytocompatibility, and Antibacterial Activity - Hu, Youdong; Zhou, Hualan; Liu, Tingting; Yang, Minhui; Zhang, Qiuyang; Pan, Changjiang; Lin, Jiafeng (Frontiers in Bioengineering and Biotechnology, 2022)
Zinc ions (Zn2+) is a highly potent bioactive factor with a broad spectrum of physiological functions. In situ continuous and controllable release of Zn2+ from the biomaterials can effectively improve the biocompatibility and antibacterial activity. In the present study, inspired by the adhesion and protein cross-linking in the mussel byssus, a one-step metal-catecholamine assembled strategy was developed to prepare a biomimetic dopamine-Zn2+ (DA-Zn2+) coating through immersing the titanium plate with the titanium oxide nanotube (TNT) arrays prepared by anodic oxidation into an aqueous solution containing dopamine (DA) and zinc ions (Zn2+). The DA-Zn2+ coatings with different zinc content exhibited excellent hydrophilicity. Due to the continuous release of zinc ions from the DA-Zn2+ coating, the coated titanium oxide nanotubes displayed excellent hemocompatibility characterized by platelet adhesion and activation and hemolysis assay. Moreover, the DA-Zn2+ coated samples exhibited an excellent ability to enhance endothelial cell (EC) adhesion and proliferation. In addition, the DA-Zn2+ coating can also enhance the antibacterial activity of the nanotubes. Therefore, long-term in situ Zn2+ releasing coating of the present study could serve as the bio-surfaces for long-term prevention of thrombosis, improvement of cytocompatibility to endothelial cells and antibacterial activity. Due to the easy-operation and strong binding ability of dopamine on various complicated shapes, the method of the present study can be further applied to other blood contact biomaterials or implantable medical devices to improve biocompatibility.